Respiratory 4D-Gating F-18 FDG PET/CT Scan for Liver Malignancies: Feasibility in Liver Cancer Patient and Tumor Quantitative Analysis - Cheung, Anson H. Y.; Wu, Vincent W. C.; Cheung, Andy L. Y.; Cai, Jing (Frontiers in Oncology, 2022)
Purpose: To evaluate the potential clinical role and effectiveness of respiratory 4D-gating FDG F-18 PET/CT scan for liver malignancies, relative to routine (3D) F-18 FDG PET/CT scan. Materials and Methods: Patient with history of liver malignancies who have undergone PET/CT exam were recruited. Liver lesions were compared in terms of 1) volume measurement of PET image, 2) accuracy of maximum standardized uptake value (SUVmax), mean standardized uptake value (SUVmean) and 3) accuracy of total lesion glycoses (TLG) in the gated and ungated image sets. Statistical analysis was performed with a two-tailed, pair t-test and Pearson correlation coefficient. Ethical approvals were obtained from ethics committees of the Hong Kong Baptist Hospital and Hong Kong Polytechnic University. Results and discussion The study population consisted of 16 patients (9 males & 7 females; mean age of 65) with a total number of 89 lesions. The quality of gated PET images was better than that of the ungated PET images. An average of 21.48% (p<0.001) reduction of the tumor volume measurement was also observed. The SUVmax and SUVmean of gated PET images improved by 19.81% (p<0.001) & 25.53% (p<0.001) compared to ungated PET images. Conclusions 4D PET/CT scan for liver malignancies in routine PET/CT examination is feasible. 4D PET/CT scan for liver malignancies could improve the quality of PET image by improving the SUV accuracy of the lesions and reducing image blurring. The improved accuracy in the classification and identification of liver tumors with 4D PET image has led to its increased utilization in target delineation of GTV, ITV and PTV for liver radiotherapy treatment planning.